Perbandingan Pertumbuhan Jamur Tiram Putih di Kumbung Ciseeng dan Universitas Al-Azhar Indonesia - Putri Kenanga; Arief Pambudi; Riris L. Puspitasari (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
White oyster mushroom (Pleurotus ostreatus) is one of wood fungi which easy to grow at rotting wood and organic waste. White oyster mushroom is rich in protein, carbohydrates, minerals, and vitamins. Environmental factors affecting the growth of white oyster mushrooms is temperature and humidity. The study aims to compare the growth and production of white oyster mushroom in different location, Ciseeng and University of Al-Azhar Indonesia (UAI). Cultivation in UAI done in a controlled situation using autoclave sterilization, inoculation using enkas and the treatment is watering on gunny sack in the mushroom house regularly. Whereas, cultivation in Ciseeng less controlled by traditional cultivation using steam sterilization and inoculation process at open space. Wet weight, dry weight, and biological efficiency results is higher in UAI than Ciseeng at 7.95%, 14.5%, and 7.34% higher, respectively. Morphological parameter such as number of fruiting body, mushroom cap diameters, and stem lenght also show better in UAI than Ciseeng at 23.67%, 8.75%, 54.96% higher, respectively. Better result of mushroom cultivation at UAI supported by 28.3oC average temperature and 93.95% humidity, meanwhile in Ciseeng average temperature and humidity was 29.25oC and 82.15%.